Perbandingan Karakteristik Demensia Vaskular dan Demensia Alzheimer di RSUD Al-Ihsan Bandung Tahun 2020-2022 - Maulavy Sofia Firdaus; Alya Tursina; Ayu Prasetia (Bandung Conference Series: Medical Science, 2024)
Abstract. Dementia is still the seventh disease that can cause death in the elderly in the world. Based on analysis data on the Global Burden of Disease (GBD) in 2050, the number of dementia cases is predicted to reach 3.4 million. The number of dementia sufferers in West Java Province is estimated to increase to 20,000 by 2025. Data related to the demographic characteristics of Alzheimer's and vascular dementia patients is very important to use as a reference for future research. This research is a cross-sectional study using 269 medical record data on the age and gender characteristics of patients with Alzheimer's dementia and vascular dementia for the period 2020-2022 at Al-Ihsan Regional Hospital, Bandung. This research was analyzed using univariate, bivariate tests and Chi-Square statistical tests. This research data was divided into two groups based on gender and age. Regarding gender characteristics, men and women, vascular dementia patients were dominated by men with a total of 137 patients (50.9%). Meanwhile, Alzheimer's dementia was found in 23 patients (8.6%) in each gender. Age characteristics are divided into three groups, namely 46-55 years old, 56-65 years old, and >65 years old. Patients with vascular dementia and Alzheimer's dementia were dominated by those aged >65 years with 106 patients (39.4%) and 30 patients (11.2%) respectively. However, the results of the Chi-Square analysis for both characteristics had a p-value >0.05. There are no differences in the characteristics of vascular dementia and Alzheimer's dementia based on gender and age at Al-Ihsan Hospital Bandung in 2020-2022. Abstrak. Demensia merupakan penyakit ketujuh yang dapat menyebabkan kematian pada lansia di dunia. Berdasarkan data analisis pada Global Burden of Disease (GBD) pada tahun 2050, capaian kasus demensia diprediksi akan menyentuh angka 3,4 juta. Jumlah penderita demensia di Provinsi Jawa Barat diperkirakan meningkat menjadi 20.000 pada tahun 2025. Penelitian ini merupakan penelitian cross-sectional dengan menggunakan 269 data rekam medis karakteristik usia dan jenis kelamin pasien demensia alzheimer dan demensia vaskular periode tahun 2020-2022 di RSUD Al-Ihsan Bandung. Penelitian ini dianalisis dengan uji univariat, bivariat, dan uji statistik Chi-Square. Data penelitian ini dibagi menjadi dua kelompok berdasarkan jenis kelamin dan usia. Pada karakteristik jenis kelamin, yaitu laki-laki dan perempuan, pasien demensia vaskular didominasi oleh laki-laki dengan jumlah 137 pasien (50.9%). Sedangkan pada demensia alzheimer diperoleh pada masing-masing jenis kelamin berjumlah 23 pasien (8.6%). Pada karakteristik usia dibagi menjadi tiga kelompok, yaitu usia 46-55 tahun, usia 56-65 tahun, dan >65 tahun. Pasien demensia vaskular dan demensia alzheimer di dominasi oleh usia >65 tahun dengan masing-masing berjumlah 106 pasien (39.4%) dan 30 pasien (11.2%). Namun, pada hasil analisis Chi-Square pada kedua karakteristik memiliki hasil p-value >0,05. Tidak adanya perbedaan karakteristik demensia vaskular dan demensia alzheimer berdasarkan jenis kelamin dan usia di RSUD Al-Ihsan Bandung Tahun 2020-2022.